The joint effects of management incentive and information precision on perceived reliability in fair value estimates. Issue 2 (19th August 2014) - Du, Ning; McEnroe, John E.; Stevens, Kevin
Abstract : Purpose: The main criticism of fair value accounting has been its lack of reliability perceived by investors. In this study we examine whether a less precise (or imprecise) estimate may increase investors' confidence and improve investors' perceptions of fair value reliability. Design/methodology/approach: We use a 2X3 randomized experiment where we manipulate management incentive and information precision. Findings: The results from this study indicate that perceived reliability is jointly affected by management's incentives and information precision. Reliability rating is the highest for fair value stated as a point estimate with a specified confidence level attached to it. Further analysis indicates that higher perceived reliability is related to its representational faithfulness because participants perceive that a point estimate with a specified confidence level better matches uncertainty in measuring future cash flows. Originality/value: This is the first study to examine whether a less precise (or imprecise) estimate may increase investors' confidence and improve investors' perceptions of fair value reliability. Because of the subjectivity and uncertainty in fair value estimates, less precise fair value estimates may not be viewed as less reliable. In fact, using a precise format to represent fair value estimates may not be appropriate (neither reliable nor credible), because a precise point estimate fails to capture its underlying uncertainty in future cash flows. A less precise format could represent a credible choice for fair value because it reflects uncertainty and subjectivity and effectively communicates management's assessments of variability in future cash flows.